1994
DOI: 10.1021/j100054a030
|View full text |Cite
|
Sign up to set email alerts
|

A Nonequilibrium Surface Barrier for Sorption Kinetics of p-Ethyltoluene on ZSM-5 Molecular Sieves

Abstract: Adsorption equilibrium and kinetic data were measured for the system p-ethyltoluene/Na,H-ZSM-5 zeolite at 343 K. The equilibrium data can be described by the superposition of two Langmuir isotherms. The kinetic data follow a complex mechanism of Fickian diffusion superimposed on the penetration of a surface barrier.The evaluation of the model parameters was carried out by simulation of sorption uptake curves including interactions of the system with both the apparatus and the intrinsic sorption kinetics. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 7 publications
(13 reference statements)
1
22
0
Order By: Relevance
“…This result suggests the existence of strong transport barriers on the crystal surface (excluding the surface of the cracks), which mainly determine the rate of adsorption/desorption. The existence of transport barriers on the external surface of ZSM-5 crystals have already been reported in a number of papers (Kärger et al, 1991;Micke et al, 1994;Wloch, 2003). As demonstrated by Figs.…”
Section: Resultssupporting
confidence: 54%
“…This result suggests the existence of strong transport barriers on the crystal surface (excluding the surface of the cracks), which mainly determine the rate of adsorption/desorption. The existence of transport barriers on the external surface of ZSM-5 crystals have already been reported in a number of papers (Kärger et al, 1991;Micke et al, 1994;Wloch, 2003). As demonstrated by Figs.…”
Section: Resultssupporting
confidence: 54%
“…(iv) Nonequilibrium barrier (Micke et al, 1994). Adsorption at the surface may not be an instantaneous equilibrium process.…”
Section: Surjace Barriersmentioning
confidence: 99%
“…The external resistance is associated to nonequilibrium sorption conditions at the surface. Micke and coworkers (Micke et al, 1994) used Langmuir kinetics to model this phenomenon. Their model leads to a pseudo surface barrier at the particle surface, with k , being concentration-dependent:…”
Section: -0mentioning
confidence: 99%
“…Bülow et al (1980) measured uptake curves of n-hexane in MgA zeolites and were able to dissociate intracrystalline and surface resistance from experiments with different crystal sizes. Micke et al (1994) showed that the uptake curves of p-ethyltoluene in Na, H-ZSM-5 cannot be correctly modelized without taking into account a surface barrier. After etching the surface of ZSM-5 crystals with fluorhydric acid, Wloch (2003) recorded an important increase of the mass transfer rate, thus confirming the existence of a surface barrier.…”
Section: Introductionmentioning
confidence: 99%